The influence of ineffective monitoring, internal audit and cost control on the financial performance of BUMDes in Sawan District - Luh Parsini Dewi; Musmini, Lucy Sri (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2024)
This research aims to understand the influence of ineffective monitoring, internal audits and cost control on the financial performance of BUMDes in Sawan District. The research that will be used in this research is quantitative research. Data collection was carried out by distributing questionnaires, then the data was processed using the SPSS application. The collected data will be tested using descriptive statistical analysis, instrument testing, classical assumption testing and hypothesis testing. The total number of respondents was 64 BUMDes administrators in Sawan District. The results of this research are that (1) ineffective monitoring (X1) plays a negative and substantial role in the financial performance of BUMDes (Y) with the significance test obtained at t with a value of 0.002 which means less than 0.05 and B has a negative sign with a value of -0.457 . (2) internal audit (X2) plays a positive and substantial role in the financial performance of BUMDes (Y) by obtaining a significance test of t with a value of 0.000, which means less than 0.05 and B has a positive sign with a value of 0.476. (3) cost control (X3) plays a positive and substantial role in the financial performance of BUMDes (Y) by obtaining a significance test of t with a value of 0.000, which means less than 0.05 and B has a positive sign with a value of 0.287.